2000
DOI: 10.1034/j.1399-3003.2000.15.33.x
|View full text |Cite
|
Sign up to set email alerts
|

Montelukast and Churg-Strauss syndrome

Abstract: In the past few months, there have been several reports about zafirlukast and Churg-Strauss syndrome [1±3]. Montelukast is a new leukotriene receptor antagonist. We report a case of Churg-Strauss syndrome while the patient was on montelukast treatment.A 25-yr-old female nonsmoker with a 6-yr history of asthma and rhinitis was admitted to the author's hospital in December 1998. She had had fever of up to 398C, malaise, headache and chest discomfort for a week. She had been treated with inhaled budesonide or flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 4 publications
(5 reference statements)
0
11
0
Order By: Relevance
“…Many cases of CSS have been reported during postmarketing surveillance of zafirlukast, 12,21-28 pranlukast, 20,29 -31 and montelukast, 9,20,28,[32][33][34][35][36][37][38][39][40][41] but only 1 such case has been mentioned after zileuton therapy, 9 but has not yet been published as a case report. Communications have indicated that more than 100 cases of CSS associated with LTRA have been reported to the US Food and Drug administration, 42,43 while their manufacturers have independently added a warning to the drug labels and have even issued a letter to physicians.…”
Section: Lma and Css: Epidemiology And Characteristicsmentioning
confidence: 97%
“…Many cases of CSS have been reported during postmarketing surveillance of zafirlukast, 12,21-28 pranlukast, 20,29 -31 and montelukast, 9,20,28,[32][33][34][35][36][37][38][39][40][41] but only 1 such case has been mentioned after zileuton therapy, 9 but has not yet been published as a case report. Communications have indicated that more than 100 cases of CSS associated with LTRA have been reported to the US Food and Drug administration, 42,43 while their manufacturers have independently added a warning to the drug labels and have even issued a letter to physicians.…”
Section: Lma and Css: Epidemiology And Characteristicsmentioning
confidence: 97%
“…Summarizing the case reports, the management of LTRA-induced CSS consisted of discontinuing the use of montelukast and the uptake of systemic corticosteroids, such as mometasone [20,32,34,37] and methylprednisolone [19,21,25,26,35]. Some authors managed CSS adding the immunosuppressive drugs cyclophosphamide and azathioprine to the steroids [21,26,32], while Villena et al [19] treated their patient with antibiotics and methylprednisolone.…”
Section: Immune System Disordersmentioning
confidence: 99%
“…Many patients were on salmeterol or salbutamol plus fluticasone propionate [19,21,24,26,27,32,38,39]. In some cases, the drugs taken by the patient included salbutamol, nedocromil, theophylline and beclomethasone [31].…”
Section: Immune System Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on clinical observations, the most widely favoured hypothesis put forward so far to explain the potential link between LTRA and CSS stipulated that LTRA administration allows tapering of corticosteroids needed to treat the asthma, thereby coincidentally unmasking a latent form of CSS 6 8. However, that theory conflicted with reports of LTRA-associated CSS occurring in the absence of concomitant corticosteroid reduction,3 1115 the overall modest corticosteroid-sparing effect of LTRA16 and the few similar observations made for drugs more potent at reducing oral corticosteroid doses such as inhaled corticosteroids 17 – 21. Most importantly, only rare observational studies sought to determine whether a real association exists between LTRA and CSS 22…”
mentioning
confidence: 99%